177Lu-FAPI Therapy in a Patient With End-Stage Metastatic Pancreatic Adenocarcinoma. (13th March 2022) - Kaghazchi, Fatemeh; Aghdam, Ramin Akbarian; Haghighi, Shirin; Vali, Reza; Adinehpour, Zohreh
Abstract: A 52-year-old woman with metastatic pancreatic adenocarcinoma underwent imaging with 18 F-FDG PET/CT and 68 Ga-FAPI-46 PET/CT, which demonstrated malignancy recurrence in the surgical bed with multiple metastatic lesions, more extensive on 68 Ga-FAPI-46 PET/CT. The patient was a candidate for therapy with 177 Lu-FAPI-46 due to high uptake of lesions in 68 Ga-FAPI-46 images and no other available therapeutic option. Posttreatment 177 Lu-FAPI-46 scans showed rather rapid washout of the radiopharmaceutical from tumoral lesions. This case report suggests that, although 68 Ga-FAPI-46 is a promising agent for tumor imaging, 177 Lu-FAPI-46 may not be an optimal compound for theranostic applications.